Fundamental Of Entrepreneurship SAPATOS / Nuratikah Kaslan ... [et al.] - Kaslan, Nuratikah; Ismail, Nurul Shahera; Ruslan, Shaznira; Mohd Yusuf, Nur Athirah; Raie, Nurul Syafinaz (2014)
Business plan is very important because it explains the content of our business. The main of business plan are marketing plan, operations plan, administrative plan and financial plan. People who have entrepreneurship knowledge will be easy for them to conduct a new business from business plan. It gives information about the business itself and guides them to run the business smoothly. The name of our shop is “SAPATOS” that we are picked from Portuguese language. The meaning of Sapatos is shoes that are show that our business is about shoes. We will open our shop at at Lot 514 & 515, Seksyen 6, Jalan Kulas, 93400 Kuching, Sarawak and will be operating on 1st January 2015. We are decided to build our business as a partnership. Partnership is the best option for us to start the business because a lot of ideas, talents and skills can be pooled together for better management. Besides that, the responsibility of managing and handling the business can be divided equally among partners. As we had agreed in our agreement letter, each of us contributed certain amount of capital to open up our business. I n cases of profits and losses, each partners will share the burden together, but if one of our partner do not want responsible legal action will be imposed.